Impacts of Immunometabolism on Male Reproduction - Ye, Lijun; Huang, Wensi; Liu, Su; Cai, Songchen; Hong, Ling; Xiao, Weiqiang; Thiele, Kristin; Zeng, Yong; Song, Mingzhe; Diao, Lianghui (Frontiers in Immunology, 2021)
The physiological process of male reproduction relies on the orchestration of neuroendocrine, immune, and energy metabolism. Spermatogenesis is controlled by the hypothalamic-pituitary-testicular (HPT) axis, which modulates the production of gonadal steroid hormones in the testes. The immune cells and cytokines in testes provide a protective microenvironment for the development and maturation of germ cells. The metabolic cellular responses and processes in testes provide energy production and biosynthetic precursors to regulate germ cell development and control testicular immunity and inflammation. The metabolism of immune cells is crucial for both inflammatory and anti-inflammatory responses, which supposes to affect the spermatogenesis in testes. In this review, the role of immunometabolism in male reproduction will be highlighted. Obesity, metabolic dysfunction, such as type 2 diabetes mellitus, are well documented to impact male fertility; thus, their impacts on the immune cells distributed in testes will also be discussed. Finally, the potential significance of the medicine targeting the specific metabolic intermediates or immune metabolism checkpoints to improve male reproduction will also be reassessed.